Pengaruh Variasi Holding Time Peleburan terhadap Karakteristik Logam Al-Si Menggunakan Cetakan Pasir - Muhammad Taufiq; Murjito Murjito; Dini Kurniawati (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2018)
Molten metal is a method to form metal to be base material of making equipment and give great advantages to human life. Purpose of this research is to find out impact value, hardness, macro defect, and micro structure as the result of holding time in molten Al-Si. Impact value of Al-Si due to molten holding time by variation of 0, 10,20, and 30 minutes are respectively 0.37 joule/mm2, 0.29 joule/mm2, 0.30 joule/mm2, and 0.26 joule/mm2. Meanwhile, hardness value of 0, 10, 20, and 30 minutes holding time are respectively 65.886 kg/mm2, 81.681 kg/mm2, 88.86 kg/mm2 and 86.265 kg/mm2. Brittle fracture occurred in all specimens and granule size of micro structure is smaller with the holding time. This research confirms that impact value has inverted correlation to hardness value. The lower of impact value, the higher hardness value. Based on micro structure observation on Al-Si casting due to molten holding time in 0, 10, 20, and 30 minutes variation, it is obtained smaller granule size.